2017
DOI: 10.1155/2017/8415979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rebonding on the Bond Strength of Orthodontic Tubes: A Comparison of Light Cure Adhesive and Resin-Modified Glass Ionomer Cement In Vitro

Abstract: The purpose of this study was to determine the impact of different enamel preparation procedures and compare light cure composite (LCC) and resin-modified glass ionomer (RMGI) on the bond strength of orthodontic metal tubes rebonded to the enamel. Twenty human molars were divided into two groups (n = 10). Tubes were bonded using LCC (Transbond XT) in group 1 and RMGI (Fuji Ortho LC) in group 2. The tubes in each group were bonded following manufacturers' instructions (experiment I) and then debonded using test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This finding was not statistically significant and these teeth were not amongst the highest-scored SBS value nor did they score a value exceeding 20 to 25 MPa, the force at which enamel fracture may occur during debonding. 27 Also, although all the samples were inspected for any cracks or deficiency before testing, these samples may have failed in this manner because of preexisting deficiencies or because the sample became desiccated during testing.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was not statistically significant and these teeth were not amongst the highest-scored SBS value nor did they score a value exceeding 20 to 25 MPa, the force at which enamel fracture may occur during debonding. 27 Also, although all the samples were inspected for any cracks or deficiency before testing, these samples may have failed in this manner because of preexisting deficiencies or because the sample became desiccated during testing.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] It can be attributed to the remaining adhesives on the enamel and thereby reducing the bond strength during rebond. [ 8 9 ] However, some studies reported similar rates of SBS for bond and rebond;[ 10 ] even some reported higher rates for rebond. [ 11 12 ] Hence, rebonding requires appropriate surface conditioning to remove remaining adhesive to achieve an acceptable level of SBS.…”
Section: Introductionmentioning
confidence: 99%
“…LED technology is used for the polymerization of light-initiated dental materials 2. LEDs use junctions of doped semiconductors to generate light.…”
Section: Introductionmentioning
confidence: 99%